Kryzys społecznej gospodarki rynkowej w kontekście procesów globalizacji - Dylus, Aniela (Annales. Etyka w Życiu Gospodarczym, 2011)
In the context of globalization processes, the social market economy (SME) is in the crisis. Reflection on the features of that model is closely related with the scientific dispute over its designation. It could be perceived as a theory, political program, sort of economic order, structure, model or system of economic and social development. Sometimes it is seemed as an idealistic vision or even political utopia (Niklas Luhmann). Others (eg. Peter Koslowski) argue that this system has come to an end. In favor of this thesis they refer to various arguments: lack of consensus on redistribution, demographic crisis, depletion of solidarity resources, intergenerational imbalance that threatens the retirement systems and many others. Despite the range of these arguments, it appears that the SME still has a specific potential that could be freed. Combating difficulties associated with globalization processes such as: dominance of the economy over politics, ‘tax starvation’ of the welfare state, marginalization of trade unions, dispersion of ownership and its detachment from responsibility, ‘financialization’ of economy, dominance of ‘casino capitalism’, could help to heal SME. The crisis on financial markets might be paradoxically an opportunity to return to the ethical foundations of the SME.